By the Numbers: Focus on the Facts - University of Wisconsin-La Crosse (University of Wisconsin-La Crosse, 2006)
Does it Mean Anything? How U.S. News Ranks Universities (September 2006) Editor's Note: This issue focuses on the U.S. News and World Report ranking of colleges and universities, which is arguably the most well known of the various publisher released rankings. It is not, however, the only ranking of schools. The Princeton Review conducts several annual surveys used to rate and rank colleges and programs—including their annual “Party School” rankings—and Thompson Peterson’s annual survey provides data for the College Search feature on Yahoo.com.
Keywords: University of Wisconsin-La Crosse -- Statistics